Healthy business : managing services in healthcare systems - Brennan, Ross, 1957-; Canning, Louise; McDowell, Raymond (London : SAGE Publications Ltd, 2017)
Healthcare systems around the world vary in terms of the mix of public sector and commercial operators and the way in which medical care is structured. This structure and mix will continue to evolve as service providers rethink their systems to achieve cost improvements, implement leaner operational processes and use quality of medical care and patient experience as their point of differentiation.
Originally published in Brennan, R., Canning, L., & McDowell, R. (2014). Healthy Business. Business-to-business marketing (3rd ed., pp. 5355). London: SAGE Publications Ltd. Print. ISBN: 9781446273722.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Health services administration